The effect of occupational coping self-efficacy on presenteeism among ICU nurses in Chinese public hospitals: a cross-sectional study - Wu, Jijun; Li, Yuxin; Lin, Qin; Zhang, Jiquan; Liu, Zhenfan; Liu, Xiaoli; Rong, Xian; Zhong, Xiaoli (Frontiers in Psychology, 2024)
Background: Nurses are the largest occupational group in the health field, with inestimable value in realizing universal health coverage, and nurses' physical and mental health has become an ordinary global reality. Compared with explicit absence, nurses' presenteeism has a more lasting impact and significant harm and loss. It has become an essential factor affecting nurses' physical and mental health, declining quality of healthcare services, and elevated healthcare-related risks. There is a lack of research exploring whether occupational coping self-efficacy influences nurses' presenteeism behavior, especially in less-developed regions of China.Objective: This study aimed to investigate the current status of ICU nurses' occupational coping selfefficacy and presenteeism in public hospitals in western China and to explore the impact of ICU nurses' occupational coping self-efficacy on presenteeism.A cross-sectional research design selected 722 ICU nurses in western China from January to February 2023 as survey respondents. A general information questionnaire, Occupational Coping Self-Efficacy Scale (OCSE-N), and Stanford Presenteeism Scale (SPS-6) were used. SPSS 21.0 software was used for statistical analysis. Pearson correlation analysis and multivariate hierarchical regression were used to explore the influence of ICU nurses' occupational coping self-efficacy on presenteeism.Results: A total of 722 ICU nurses completed the questionnaire. The OCSE-N score of ICU nurses was (22.24±6.15), and the SPS-6 score was (16.83±4.24). The high presenteeism was 67.23%.Correlation analysis showed that in ICU nurses, OCSE-N total score was negatively correlated with SPS-6 total score (r=-0.421, P<0.05), indicating that the higher the level of occupational coping selfefficacy, the lower the presenteeism. Multiple hierarchical regression analysis showed that occupational coping self-efficacy strongly predicted presenteeism, accounting for approximately 18.35% of the total variance.There is a correlation between ICU nurses' occupational coping self-efficacy and presenteeism, and nurses' occupational coping self-efficacy affects presenteeism differently.Managers should pay attention to nurses' occupational coping self-efficacy to promote nurses' presenteeism reduction.